Study Kasus Bullying Terhadap Dampak Psikologis Anak Usia SMP Pondok Pesantren Kubu Raya - Fitri Pratiwi; Aunurrahman Aunurrahman; Halida Halida (Departement of Mathematics Education, 2023)
Bullying is bad behavior carried out by a person or group repeatedly with the intention of hurting someone. It is hoped that parents can shape the character of their children at Islamic boarding schools so they can learn religious knowledge. Bullying is one of the biggest sins in education that still occurs today. The researchers conducted research with the aim of finding out the psychological impact of students and finding out the causes of bullying at the Kubu Raya Islamic Boarding School. This type of research uses qualitative research with a library research approach. The techniques used were interviews and observations of bullying cases which had an impact on the psychology of students at the Kubu Raya Islamic boarding school. Based on the research results, it can be concluded that victims of bullying prefer to remain silent when being bullied, because they are afraid of being bullied who will hurt themselves and the victim has difficulty reporting the incident to a caregiver or teacher. This makes victims of bullying harbor feelings of hurt, anger or pent-up emotions and will have difficulty making friends. One other way victims of bullying do this is to be alone. The boarding school students will carry out activities alone or the victims of bullying do not have many friends.